1999
DOI: 10.3354/dao036153
|View full text |Cite
|
Sign up to set email alerts
|

Yellow head virus from Thailand and gill-associated virus from Australia are closely related but distinct prawn viruses

Abstract: Corresponding genomic regions of isolates of yellow head virus (YHV) from Thailand and gill-associated virus (GAV) from Australia were compared by RT-PCR and sequence analysis. PCR primers designed from sequences in the GAV ORFlb polyprotein gene amplified the corresponding 577 nucleotide region of the YHV genome. Comparison of the amplified region indicated 85.1 % nucleotide and 95.8% amino acid sequence identity. YHV PCR primers designed to amplify a 135 nucleotide product previously described as a YHV &agno… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
87
1

Year Published

2000
2000
2021
2021

Publication Types

Select...
6
2
1

Relationship

3
6

Authors

Journals

citations
Cited by 80 publications
(89 citation statements)
references
References 12 publications
1
87
1
Order By: Relevance
“…Recent molecular studies of YHV and GAV have shown that they are closely related but distinct viruses which are likely to be classified in the family Coron-aviridae (Cowley et al 1999). Wongteerasupaya et al (1995) demonstrated that YHV contains a singlestranded RNA genome.…”
Section: Introductionmentioning
confidence: 99%
“…Recent molecular studies of YHV and GAV have shown that they are closely related but distinct viruses which are likely to be classified in the family Coron-aviridae (Cowley et al 1999). Wongteerasupaya et al (1995) demonstrated that YHV contains a singlestranded RNA genome.…”
Section: Introductionmentioning
confidence: 99%
“…It is an enveloped, rod-shaped virus approximately 706180 nm in size (Chantanachookin et al, 1993;Flegel et al, 1995;Wongteerasupaya et al, 1995) and is classified as the type species of the genus Okavirus, family Roniviridae, in the order Nidovirales (Cowley et al, 1999;Walker et al, 2005;Ziebuhr et al, 2003). The YHV genome comprises a positive-sense, 26 662 nt ssRNA containing four ORFs designated ORF1a, ORF1b, ORF2 and ORF3 (Sittidilokratna et al, 2008;Wongteerasupaya et al, 1995).…”
Section: Introductionmentioning
confidence: 99%
“…It has been established previously that GAV from Australia and YHV from Thailand are distinct but closely related viruses (Spann et al 1997, Cowley et al 1999. P. monodon is a natural host of both GAV in Australia and YHV in Thailand.…”
Section: Abstract: Gill-associated Virus Gav · Penaeid Prawn · Diseasementioning
confidence: 99%
“…GAV and YHV virions are rod-shaped, enveloped particles containing helical nucleocapsids that mature by budding at intracytoplasmic membranes , Spann et al 1997. Nucleotide sequence comparisons of the putative polymerase (ORF1b) genes have indicated that GAV and YHV are closely related but distinct viruses and are likely to be classified in the order Nidovirales, possibly in the family Coronaviridae (Cowley et al 1999(Cowley et al , 2000a.…”
mentioning
confidence: 99%